Polycystic ovarian syndrome and insulin resistance: a North Indian study - Agarwal, Nitin; Gangopadhyay, Sukanya; Koch, Nirensingh; Gupta, Akash; Batra, Aruna; Kabi, B. C. (International Journal of Research in Medical Sciences, 2017)
Background: Polycystic ovarian syndrome (PCOS) is most common form of chronic anovulation associated with androgen excess. Insulin resistance (IR) is characterized by impaired glucose response to specific amount of insulin. The objective of the study was to find an association between PCOS and IR in North Indian patients. Methods: A total of 50 PCOS cases diagnosed according to Rotterdam criteria, 2003, i.e. at least two of the following three features: oligomenorrhea or amenorrhea, clinical or biochemical hyperandrogenism and polycystic ovaries on ultrasound. Serum glucose levels were measured spectrophotometrically by glucose oxidase-peroxidase method. Insulin levels in serum were estimated by using ELISA based kit procured form Diasorin Ltd, Germany. Homeostatic Model Assessment- Insulin Resistance (HOMA-IR) and Body Mass Index (BMI) were calculated by their formulas. Results: PCOS patients had significantly higher values of BMI, fasting serum glucose, fasting serum insulin and HOMA-IR. Fasting serum glucose was however in the normal range in both cases and control. Conclusion: Our study suggested a strong association of PCOS with insulin resistance in this part of the country.